Model of Legal Aid Scheme Against Sexual Violence for Deaf and Speech Impaired Women with Disabilities: Model Skema Bantuan Hukum Terhadap Kekerasan Seksual Bagi Perempuan Disabilitas Tuna Rungu dan Tuna Wicara - Zahra Mauludina; Brian Marcelino; Choirunnisa Adlea; Syatriawan Lagura; Rayyan Alkhair (Universitas Negeri Semarang, 2022)
A case of sexual violence experienced by a deaf and speech impaired person in Makassar who was raped by three men and blackmailed into giving money worth five million with the threat that if not given, the rape video would be distributed. In this case, it is difficult for the victim to provide information when going through a criminal trial process, because most of the existing Legal Aid Institutions are not equipped with translators for people with disabilities. Seeing the various forms of problems in handling sexual violence, improvements should be made in handling cases of sexual violence for victims with disabilities: First, Legal-formal legal assistance from LBH APIK Advocates, Second, Psychological personal assistance by adult clinical psychologists from before to the end of the trial, Third, Assistance by a sign language interpreter during the trial to be able to help provide information at the trial and 4). Create a Victim Trust Fund for victims of sexual violence to meet the material and immaterial needs of victims.